What can you see? in the country - Grundy, Lynn N.; Grundy, Lynn N.; Grandreams Ltd. (London Grandreams Ltd., 1994)
A visually engaging book that helps children identify and learn about different scenes and objects commonly found in the countryside. Features large illustrations and simple text to encourage early learning and vocabulary development.
Book format with bright and engaging illustrations; designed for early readers and young children to build vocabulary and observation skills.
For children aged 2-5. Suitable for EYFS/Pre-K/Kindergarten level.
Keywords: Country life-Vocabulary-Nature-Animals